Prophet of the Electric Age: Cultural Performativity as Nonviolent Revolution in the Lifework of Percy Bysshe Shelley - Devenot, Neşe (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
This article examines Percy Bysshe Shelley’s interest in contemporary possibilities of text dissemination in order to reconcile the normally opposing tendencies of gradualism (“slow reform”) and “violent” revolution in his life and writings. I offer a close reading of two parallel cultural events, both of which produced a national commotion that widely disseminated radical views—the “Peterloo” massacre at Manchester and Lord Eldon’s copyright rulings as Lord Chancellor. In both instances, the government’s attempts to control expression had the opposite effect due to the consequences of press coverage and political activism. In combination with nonviolent textual piracy, I argue that the circulation of the belief in poetry’s power concomitantly with the formation of a radical canon encouraged the latter’s circulation as propaganda, de facto establishing a common cultural heritage for the growing radical movement. Since Shelley’s writings became a fundamental component of the cultural glue that encouraged cohesion of the expanding radical class as soon as one decade after his premature death, I suggest that a reading of Shelley’s political strategies that moves beyond “ineffectualism” can highlight the continuing relevance of Shelley’s aesthetics and political thought.